The Causal Relationship Model of Continuing Accounting Professional Development and Technology Adaptation Affecting Accounting Software Package Usage Skill and Accountant’s Personal Values of Accounting Firms in Northern Thailand - Wongjinda, Chawiang; Ratanasongtham, Worapan; Homphian, Nunmanus (Journal of Business, Innovation and Sustainability (JBIS), 2023)
This research aims to investigate the causal relationship model of continuing accounting professional development and technology adaptation affecting accounting software package usage skill and accountant’s personal values, by using a questionnaire as an instrument for collecting data from 385 accountants of accounting firms in Northern Thailand. All composite reliability values ranged from 0.939 to 0.955. The data was analyzed by SEM using Lisrel. The results show that technology adaptation was the most influential factor directly on the accounting software package usage skills and indirectly on the personal values, with the mediator being accounting software package usage skill. The results also show that the measurement model was in congruence with the empirical data (χ2 = 145.075, p-value = 0.506, df= 146 (χ2/df = 0.993), RMSEA = 0.000, GFI = 0.962, AGFI = 0.954, NFI = 0.968, NNFI = 0.995). This model exhibits goodness of fit.